Circular economy meets water treatment: one-pot synthesis of agricultural waste-based bi-functionalized ordered mesoporous silica for tetracycline removal via systematic adsorption studies - Wenli Gou; Sameer Alshehri; Niloofar Pirestani; Soroosh Soltani; Ahmadreza Roghanizad; Saeed Shirazian; Roozbeh Soltani (Applied Water Science)
Abstract This research endeavors to elucidate the process of developing and characterizing a novel plant-derived biogenic-based bi-functionalized MCM-41 (Mobil Composition of Matter No. 41), abbreviated as Bif-MCM-41, prepared through an environmentally friendly one-pot method. The Bif-MCM-41 material was functionalized with two different silane coupling agents with different functional groups to enhance its adsorption properties. XRD and TEM confirmed the mesoporous structure constructed from well-ordered hexagonal arrays of parallel microchannels, while FESEM revealed uniform Bacillus-like (rod-shaped) morphology. The material exhibited a high surface area (988 m2 g−1), a pore volume of 0.72 cm3 g- 1 and a bimodal pore distribution (1.3 nm and 2.5 nm) based on 2D-NLDFT method, confirming a well-developed micro-mesoporous structure. Adsorption studies for tetracycline were conducted under varying conditions, and both linear and nonlinear isotherm and kinetic models were applied to assess adsorption behavior. The maximum Langmuir adsorption capacity reached 765.4 mg g−1 at 293 K. Nonlinear fitting provided a more accurate representation of adsorption behavior, and kinetic studies indicated a pseudo-first-order mechanism, suggesting surface reaction dominance. Thermodynamic analysis confirmed the process as spontaneous and exothermic, driven by π–π stacking and hydrogen bonding. The combination of biogenic synthesis, dual functionalization, and outstanding adsorption performance represents a unique contribution to the development of sustainable adsorbents. This study offers both mechanistic insight and practical relevance, bridging green chemistry with high-efficiency pollutant removal.